The Adaptation of the Students’ Beliefs About Peer Feedback Scale İnto Turkish: A Validity and Reliability Study - İhtiyaryer, Begüm; Alcı, Bülent (Siree Publications, 2021)
The purpose of this research is to adapt the Students’ Beliefs about Peer-feedback Scale developed by Huisman (2018) into Turkish and study validity and reliability in the adapted scale. After the linguistic equivalence study, the form was filled by 100 university students who study at English preparatory school. The EFA showed that the total explained variance was 67% and the items in the scale were loaded under 3 factors. The CFA confirmed the factors determined in EFA. The reliability study indicated that the Cronbach alpha coefficient was .80.According to the item analysis, t test results between 27% upper and lower groups were statistically significant. Finally, the two halves of the scale were found to be correlated at .59 level. As a result, this study showed that ‘The Students’ Beliefs about Peer Feedback scale’ was a valid and reliable scale to measure students’ beliefs on peer-feedback in the Turkish context.
Keywords: Peer-Feedback; Students’ Beliefs; Feedback